2019
DOI: 10.1128/aem.02815-18
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Expression and Characterization of Gassericin T and Gassericin S, a Novel Class IIb Bacteriocin Produced by Lactobacillus gasseri LA327

Abstract: Lactobacillus gasseri LA327, isolated from the large intestine tissue in humans, is a bacteriocinogenic strain with two kinds of class IIb bacteriocin structural genes, i.e., those for gassericin T (GT) and acidocin LF221A (Acd LF221A). In this study, DNA sequencing of the genes for GT and Acd LF221A from L. gasseri LA327 revealed that the amino acid sequences for GT corresponded with those for GT genes, except for GatK (histidine kinase). However, Acd LF221A genes had analogues which differed in at least one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…1a). Bact_1 and Bact_2 show 100% amino (Kasuga et al 2019), while the surrounding genes do not resemble any other genes associated with bacteriocin production. The putative immunity protein showed 97% amino acid homology to those of the acidocin LF221A and gassericin S clusters (Kasuga et al 2019;Majhenič et al 2004).…”
Section: Identification Of Bacteriocin Gene Clusters In the Genome Ofmentioning
confidence: 94%
See 2 more Smart Citations
“…1a). Bact_1 and Bact_2 show 100% amino (Kasuga et al 2019), while the surrounding genes do not resemble any other genes associated with bacteriocin production. The putative immunity protein showed 97% amino acid homology to those of the acidocin LF221A and gassericin S clusters (Kasuga et al 2019;Majhenič et al 2004).…”
Section: Identification Of Bacteriocin Gene Clusters In the Genome Ofmentioning
confidence: 94%
“…The gassericin E operon was identified in L. gasseri EV1461, isolated from the vagina of a healthy woman; it encodes both antimicrobial gassericin E, with high similarity to gassericin T, and gene gaeX, whose product is identical to GatX and gassericin K7 B (Maldonado-Barragán et al 2016). Recently, genes encoding gassericin T (GatA and GatX) and the novel gassericin S, with similarity to acidocin LF221A (GasA and GasX), were found in the genome of L. gasseri LA327, isolated from the colon of a human adult (Kasuga et al 2019). This study demonstrated synergistic activity between the two components of gassericin T, and those of gassericin S, but not between gassericin S and gassericin T (Kasuga et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bact_2), respectively (Kasuga et al, 2019). While Bact_1 and Bact_2 showed synergistic activity, the 509…”
mentioning
confidence: 94%
“…Finally, genes encoding gassericin T (GatA and GatX) and the novel 95 gassericin S, with similarity to acidocin LF221A (GasA and GasX), were all found in the genome of L. 96 gasseri LA327, isolated from human large intestine tissue (Kasuga et al, 2019). Kasuga et al 97 demonstrated the synergistic activity between the two components of gassericin T, and those of 98 gassericin S (Kasuga et al, 2019). However, they could not demonstrate synergistic activity between 99 gassericin S and gassericin T when they mixed the four peptides together.…”
mentioning
confidence: 99%